2009
DOI: 10.1684/epd.2009.0244
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after vagal nerve stimulator insertion

Abstract: Aim. Assess quality-of-life after vagal nerve stimulation and determine patient characteristics associated with improvement in quality-of-life. Methods. Sixteen patients (11 children, 5 adults) who had vagal nerve stimulation at our center were studied. Quality-of-life was assessed pre-and post-vagal nerve stimulation using the Quality-of-Life in Childhood Epilepsy questionnaire for children and the Epilepsy Surgery Inventory-55 for adults. Results. Sixteen patients who did not qualify for resective surgery we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Klinkenberg and colleagues also examined QOLIE-89 scores before and 6 months after VNS in 41 adults with epilepsy, observing significant improvements in mood and overall QOL with stimulation [21]. In pediatric patients with epilepsy, a few small VNS studies have reported improved alertness or social interactions based on retrospective chart review [22, 23] or neuropsychological evaluation [24]. One investigation indirectly inferred increased quality-adjusted life years with VNS based on reduced hospitalizations recorded in U.S. Medicaid data [25].…”
Section: Discussionmentioning
confidence: 99%
“…Klinkenberg and colleagues also examined QOLIE-89 scores before and 6 months after VNS in 41 adults with epilepsy, observing significant improvements in mood and overall QOL with stimulation [21]. In pediatric patients with epilepsy, a few small VNS studies have reported improved alertness or social interactions based on retrospective chart review [22, 23] or neuropsychological evaluation [24]. One investigation indirectly inferred increased quality-adjusted life years with VNS based on reduced hospitalizations recorded in U.S. Medicaid data [25].…”
Section: Discussionmentioning
confidence: 99%
“…examined quality of life changes following VNS for refractory epilepsy and showed an improvement in the total quality of life and social indices that correlated with the reduction in seizure burden. [16] Others have reported similar beneficial effects on the quality of life assessments following VNS therapy in children. [2535] A more focused review of very young children, less than three years of age, using VNS therapy for catastrophic epilepsy and cognitive impairment suggested increases in quality of life, parental satisfaction, and even achievement of developmental milestones.…”
Section: Methodsmentioning
confidence: 87%
“…One patient was excluded from this review because of accidental death shortly after implantation, of causes unrelated to his underlying condition or the device. Mean age at implantation was 9.4 years (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Mean duration of epilepsy prior to implantation was 6.5 years.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…1 Numerous reports have established VNS therapy as a safe and effective treatment option for children and adults who have refractory epilepsy. [1][2][3][4][5][6] The cost effectiveness of VNS therapy has also been assessed and established in the developing world, 7,8 however there are very little reports on its use in developing countries, 9 and none that address cost related issues. In this report, we describe the experience with VNS therapy in children with refractory epilepsy from the two major university hospitals in Jordan, and perform an analysis of direct hospital costs and cost utility.…”
Section: Introductionmentioning
confidence: 99%